Pediatric NUT-midline carcinoma: Therapeutic success employing a sarcoma based multimodal approach. (19th May 2017) - Storck, Simone; Kennedy, Alyssa L.; Marcus, Karen J.; Teot, Lisa; Vaughn, Jennifer; Gnekow, Astrid K.; Märkl, Bruno; Leuschner, Ivo; DuBois, Steven G.; French, Christopher A.; Frühwald, Michael C.
ABSTRACT: A subset of poorly differentiated squamous cell carcinomas, NUT midline carcinomas (NMC) are characterized by a translocation t(15;19)(q13;p13) [1 ]. The prognosis is generally dismal [2 ] and therapeutic success has been limited to exceptional cases [3 ]. We present two cases of pediatric NMC from two different institutions treated according to a multimodal sarcoma approach involving surgery, chemotherapy, and focal radiotherapy. One patient has remained in complete continuous remission for over 6 years, while the other is in CR in early follow-up off therapy. Our proposed multimodal strategy apparently meets the aggressive biologic nature of NMC and should be considered for further evaluation in this context potentially in the setting of a clinical trial.